Maternal attitude towards delaying puberty in girls with and without a disability: a questionnaire-based study from the United Arab Emirates. Issue 1 (9th October 2018) - Deeb, Asma; Akle, Mariette; Al Zaabi, Abrar; Siwji, Zohra; Attia, Salima; Al Suwaidi, Hana; Al Qahtani, Nabras; Ehtisham, Sarah
Abstract : Background: Parental anxiety about the impact of puberty/menses, particularly in girls with severe disability leads to seeking therapeutic pubertal suppression. We aim to explore maternal attitudes and reasons for seeking pubertal suppression. Methods: Mothers of girls receiving gonadotropin -releasing hormone analogue therapy in Mafraq hospital, Abu Dhabi were enrolled in the study. A semistructured interview was conducted to ascertain possible reasons for delaying puberty. The study group was divided into girls with a disability with central precocious puberty (CPP) or normal puberty and girls without a disability presenting with CPP. Results: 42 mother–daughter pairs were enrolled and divided into two groups; group A: 15 girls with CPP with no disability; group B: 27 girls with disability (10 had CPP (group B1) and 17 had normal pubertal timing (group B2)). Mothers in group A aimed to delay puberty, while in group B, 13 (48%) mothers desired to halt puberty and 7 (26%) requested permanent surgical intervention. Fear of short stature (15, 100%), inability to cope psychologically (10, 67%) and fear of peer rejection (9, 60%) were the main concerns in group A. In group B, mothers were concerned about menstrual hygiene management (25, 92.5%), fear of child abuse or unwanted pregnancy (15, 55%) and fear of inability to express pain/discomfort with menstruation (8, 30%). Conclusion: Mothers of girls with a disability commonly seek medical help to delay/halt puberty due to concerns about menstrual hygiene. Short final height was the main concern for girls without a disability. Culture and religion play an important role in puberty management in girls with a disability.